Spherical Shell Bioprinting to Produce Uniform Spheroids with Controlled Sizes - Kuk Hui Son; Dong-Ha Kim; Seunghye Park; Hyun Jae Kim; Mira Park; Seung-Jin Kim; Sang Jin Lee; Keunsun Ahn; Jin Woo Lee (Journal of Functional Biomaterials)
Conventional cell spheroid production methods are largely manual, leading to variations in size and shape that compromise consistency and reliability for use in cell-based therapeutic applications. To enhance spheroid production, a spherical shell bioprinting system was implemented, enabling the high-throughput generation of uniform cell spheroids with precisely controlled sizes. The system encapsulates cells within thin alginate hydrogel shells formed through bioprinting and ion crosslinking reactions. Alginate–calcium ion crosslinking created alginate shells that contained gelatin-based bioinks with embedded cells, facilitating spontaneous cell aggregation within the shells and eliminating the need for plastic wells. By adjusting cell concentrations in the alginate–gelatin bioink, we achieved precise control over spheroid size, maintaining a sphericity above 0.94 and size deviations within ±10 µm. This method has been successfully applied to various cell types including cancer cells, fibroblasts, chondrocytes, and epithelial cells, demonstrating its versatility. This scalable approach enhances the reliability of cell therapy and drug screening, offering a robust platform for future biomedical applications.